2011
DOI: 10.1002/chem.201100910
|View full text |Cite
|
Sign up to set email alerts
|

A Metal‐Free Route to 2‐Aminooxazoles by Taking Advantage of the Unique Ring Opening of Benzoxazoles and Oxadiazoles with Secondary Amines

Abstract: Toss an amine into the ring: A new metal‐free protocol for the amination of oxazoles has been developed by using iodobenzene diacetate to couple various oxazoles with amines (see scheme). The reaction proceeds through a ring‐opening and subsequent ring‐closing pathway. The optimal conditions are very mild and the substrate scope is broad, producing a range of 2‐aminooxazoles, an important pharmacophore with high bioactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 47 publications
0
36
0
2
Order By: Relevance
“…A careful analysis of the above transformation revealed that the amine‐promoted ring‐opened azole was the major side product,9 aside from unreacted azole. In light of this, the ratio of the reactants 1 a / 2 a / 3 a was changed to 1:1.5:1.2, which enhanced the yield of 4 a to 23 % (Table 1, entry 2).…”
Section: Methodsmentioning
confidence: 99%
“…A careful analysis of the above transformation revealed that the amine‐promoted ring‐opened azole was the major side product,9 aside from unreacted azole. In light of this, the ratio of the reactants 1 a / 2 a / 3 a was changed to 1:1.5:1.2, which enhanced the yield of 4 a to 23 % (Table 1, entry 2).…”
Section: Methodsmentioning
confidence: 99%
“…2-Substituted benzoxazoles are generally synthesized by the oxidative cyclization of phenolic imines mediated by strong oxidants working in concert with transition metal catalysts, such as Pd, Cu, Fe, Ni, Ag, and Ru. [4][5][6][7][8][9][10] However, toxic metal catalysts, strong and expensive oxidants, high catalyst loading, and high reaction temperatures are required for the preparation of 2-substituted benzoxazoles in most cases. Therefore, a milder and more efficient method to prepare these compounds would be highly desirable.…”
Section: Hemoglobin: a New Biocatalyst For The Synthesis Of 2-substitmentioning
confidence: 99%
“…The resultant solution was stirred at 60 °C for 4 h. The solvent was removed in vacuo and the residue was purified by flash column chromatography on silica gel (5% ethyl acetate in petroleum ether) to afford 2-(pyrrolidin-1-yl)benzo [d] 29 To a stirred solution of 5-methoxy-2-(trichloromethyl) benzo [d]oxazole (1c, 147 mg, 0.55 mmol) in dry acetonitrile (1 M) at r.t. was added pyrrolidine (51 µL, 0.6 mmol). The resultant solution was stirred at 60 °C for 4 h. The solvent was removed in vacuo and the residue was purified by flash column chromatography on silica gel (5% ethyl acetate in petroleum ether) to afford 5-methoxy-2-(pyrrolidin-1-yl)benzo [d] 29 To a stirred solution of 5-chloro-2-(trichloromethyl) benzo [d]oxazole (1d, 150 mg, 0.55 mmol) in dry acetonitrile (1 M) at r.t. was added pyrrolidine (51 µL, 0.6 mmol). The resultant solution was stirred at 60 °C for 4 h. The solvent was removed in vacuo and the residue was purified by flash column chromatography on silica gel (5% ethyl acetate in petroleum ether) to afford 5-chloro-2-(pyrrolidin-1-yl)benzo [d] …”
mentioning
confidence: 99%